talent management and its role in Empowering employees - فخري, نور حسين (Journal of Economics and Administrative Sciences, 2019)
AbstractThe research aims at achieving a set of objectives, which is to study a vital variable in the organizations which is the talent management and its impact on encouraging and empowering employees to take part in making appropriate decisions with their heads in the Iraqi Cement State Company. The problem of this research is in finding solutions to the weaknesses that face the managers in attracting talented employees and keep them in the company, and this leads to a weak capacity of the company on authorizing talented employees and giving them the needed confidence to participate in decision making process. The research sample was included (45) managers in the researched company. This study was based on choosing assumptions of the relationship of the connection and the impact between variable talent management and empowering employees in company. At the overall level, and at the sub-dimension level, the questionnaire was the main tool in collecting data and information. The research uses statistical program (SPSS), to analysis data.The research reached some conclusions and the most important one is talent management and its distance has affects significantly in empowering employees except talent attraction dimension, This result reflects the company's ability to focus its focus on the development of talented employees, and their performance management, and preserving them, by supporting their achievements and giving them the opportunity to participate in making the necessary decisions at work, which requires the company management to pay an attention on the talented workers, and work to attract them of its competitors by providing all necessary methods to fulfill their desires and encourage them to work.